2007
DOI: 10.1002/jmv.20859
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sapovirus infection among infants and children with acute gastroenteritis in Dhaka City, Bangladesh during 2004–2005

Abstract: Sapovirus, a member of the family Caliciviridae is one of the major causative agents of viral gastroenteritis affecting all age group. Sapovirus was detected in 25 of 917 stool specimens from infants and children with acute gastroenteritis in a Children Hospital in Dhaka City, Bangladesh during 2004-2005. All fecal specimens were examined for sapovirus by reverse transcription-polymerase chain reaction. Molecular analysis of sapovirus was carried out by sequencing methods. Sapovirus detected in this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
6
20
0
Order By: Relevance
“…In contrast to this genetic variability noted among the norovirus strains, all Tunisian sapovirus sequences belonged to only one single sapovirus genotype GGI/1. The findings are in agreement with many of the earlier sapovirus studies worldwide describing sapovirus GGI/1 as the most prevalent genotype detected in pediatric gastroenteritis [13,15,17,18,20,24,39,48]. However, in other studies a genetic diversity of sapovirus strains was reported in gastroenteritis cases including genotypes of GGII, GGIII, GGIV [8,16,35].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to this genetic variability noted among the norovirus strains, all Tunisian sapovirus sequences belonged to only one single sapovirus genotype GGI/1. The findings are in agreement with many of the earlier sapovirus studies worldwide describing sapovirus GGI/1 as the most prevalent genotype detected in pediatric gastroenteritis [13,15,17,18,20,24,39,48]. However, in other studies a genetic diversity of sapovirus strains was reported in gastroenteritis cases including genotypes of GGII, GGIII, GGIV [8,16,35].…”
Section: Discussionsupporting
confidence: 93%
“…It was rarely detected in association with foodborne outbreaks [45] and it was also detected in asymptomatic infants [8] as in asymptomatic adults [39]. In contrast, two studies conducted in Bangladesh and China showed that clinical signs (diarrhea, fever, vomiting, and abdominal cramps) were associated with sapovirus infections in young children (2-38 months) and college students, respectively [15,46]. The data indicate that sapovirus causes mild gastroenteritis in children in Tunisia, while norovirus causes severe sporadic gastroenteritis and is responsible for a high number of hospitalization cases (P = 0.03).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…All fecal specimens were also tested for the presence of sapovirus, astrovirus by RT-multiplex PCR. Among diarrheal viruses detected, norovirus was the most prevalent (4.5%), followed by 2.7% of sapovirus and 0.3% of astrovirus (Dey et al, 2007). The youngest subject was 2-month-old and the oldest 38 months; the average age was 13 months.…”
Section: Detection Of Norovirusesmentioning
confidence: 97%
“…Acute gastroenteritis (AGE) is one of the most frequent diseases in children worldwide and remains the main cause of childhood morbidity and mortality, particularly in developing countries. Each year as many as 1.5 million children in the first 5 years of life die from AGE (Dey et al 2007;Fabiana et al 2007;Rahman et al 2007;Parashar et al 2006). Rotaviruses ( Fig.…”
Section: Introductionmentioning
confidence: 99%